A Study of Ideal Physical Education Teachers’ Competencies from Junior High School Students’ Perspectives - Muhammad Sukron Fauzi; Hendry Ismawan; Nurjamal Nurjamal; Alventur Baun; Muhamad Rohadi; Muhammad Saiin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the competence of the ideal Physical Education, Sports, and Health (PJOK) teacher based on the perspective of grade IX students at SMP Negeri 6 Samarinda. Teacher competence is an important aspect in supporting the success of the learning process and improving the quality of education. The ideal PJOK teacher is expected to have four main competencies, namely pedagogic, personality, professional, and social competencies that are integrated in daily learning practices. This study uses a quantitative descriptive approach with a population of 45 students in grade IX. The sampling technique uses simple random sampling to provide equal opportunities to each member of the population. Data collection was carried out through observation, questionnaires, and documentation. The data obtained was analyzed using descriptive statistical techniques. The results of the study showed that the profile of PJOK teachers at SMP Negeri 6 Samarinda was in the good category. This can be seen from students' assessments of teachers' abilities in managing learning, showing a good attitude, having professional competence, and being able to interact socially well in the school environment. In addition, PJOK teachers are also considered to be able to be role models in their daily attitudes and behaviors. Based on these findings, it can be concluded that PJOK teachers have met the criteria as ideal teachers according to the student's perspective. However, competency improvement still needs to be carried out on an ongoing basis to support a more optimal quality of learning in the future.